Coumarin Hybrids: Promising Scaffolds in the Treatment of Breast Cancer - Bhatia, Rohit; Rawal, Ravindra K. (Mini Reviews in Medicinal Chemistry, 2019)
Breast cancer is the most common invasive cancer in women, and the second main cause of deaths in women, after lung cancer. There is continuous advancement in the development of therapeutic agents against breast cancer in recent years and it is still in progress. Development of hybrid molecules by combining different pharmacophores to obtain significant biological activity is an excellent approach. Coupling of coumarin scaffold with other distinct motifs has led to the design of newer compounds against breast cancer. These distinct pharmacophores possess a diverse mode of action as well as selectivity. It has been reported in the literature that coumarin hybrids possess significant potency against breast cancer by binding to various biological targets which are associated with breast cancer. Due to low toxicity profile on various organ systems, coumarin hybrids have nowadays attracted the keen attention of researchers to explore their therapeutic ability against breast cancer. Reported coumarin hybrids include coupling with isoxazole, thiazole, monastrol, chalcone, triazole, sulphonamide, triphenylethylene, benzimidazole, pyran, imidazole, stilbene, oestrogen, phenylsulphonylfuroxan, etc. In the present review, a description of various coumarin hybrid molecules has been presented along with their structural-activity relationships.
Keywords: sulphonamide